Requirement for the NINAC Kinase/Myosin for Stable Termination of the Visual Cascade - Li, Hong-Sheng (J Neurosci, 1998)
Activation of the Drosophila photoresponse is a rapid process that results in plasma membrane Ca(2+)and Na(+) conductances. Ca(2+)functions in negative feedback regulation of Drosophilavision including deactivation. Protein kinase C (PKC) binds directly to Ca(2+) and is required for deactivation. However, the consequences of disrupting phosphorylation of any individual PKC substrate in the Drosophila retina have not been addressed. In the current work, we show that NINAC p174, which consists of a protein kinase domain joined to the head region of myosin heavy chain, is a phosphoprotein and is phosphorylated in vitro by PKC. Mutation of either of two PKC sites in the p174 tail resulted in an unusual defect in deactivation that had not been detected previously for other ninaC alleles or other loci. After cessation of the light stimulus, there appeared to be a transient reactivation of the visual cascade. This phenotype suggests that a mechanism exists to prevent reactivation of the visual cascade and that p174 participates in this process.